Conference 2016: From Drug Discovery to Health Outcomes: Population to Patient. An international symposium held jointly by CSPS and CC-CRS, May 31-June 3, 2016, Vancouver, BC, Canada - Berekoff, Beverley (Journal of Pharmacy & Pharmaceutical Sciences, 2016)
Plenaries and Special Presentations: Carolyn Buser-Doepner, GSK: "New Trends in Pharma-Academia Collaborations for Drug Discovery" Chris Halyk, President, Janssen Inc.: "Are Innovative Medicines and our Life Sciences Industry at Risk in Canada?" Aaron Schimmer, Princess Margaret Cancer Centre: "New Therapeutic Strategies to Target the Mitochondria in Leukemia" Ivana Cecic, Genome BC: "Genomics in Canada: From Knowledge Generation to Patient Outcomes" Adam Rosebrock, University of Toronto: "Quantitative Mass-Spectrometry Metabolomics for Direct Biochemical Phenotyping" Fakhreddin Jamali, University of Alberta: CSPS Lifetime Achievement Award Lecture - "Pharmaceutical Research and Development, Lessons Learned" Conference Sessions: Special Session: Innovation and Management of Modern Pharmaceuticals 1. Special Populations 2. Nanomedicines Become Personal: Opportunities and Challenges 3. Mucosal Drug Delivery 4. Broaching the Fourth Hurdle: Getting Drugs on the Formulary 5. Pharmacogenomics in the Clinic and Community 6. Responsive Drug Delivery Systems 7. Drug Targeting and Targeting Drugs 8. Health Sustainability Evidence 9. Integrating Pharmaceutical Sciences into a Pharm D Curriculum 10. Analytical Innovation to Support Precision Medicine and Biologicals Development 11. Protein and Peptide Delivery